2015
DOI: 10.1155/2015/419180
|View full text |Cite
|
Sign up to set email alerts
|

Monophasic Synovial Sarcoma of Prostatic Fascia: Case Report and Literature Review

Abstract: Synovial sarcoma (SS) primarily occurs in the para-articular soft tissue of the lower extremities in young adults and it is extremely rare in the prostatic region. We report a case of a 46-year-old man who presented with urinary retention. Pelvic ultrasound (US) examination, computed tomography (CT), and magnetic resonance imaging (MRI) demonstrated an 8.5 cm mass that appeared to originate in the prostatic fascia of the right lobe. Preoperative prostatic ultrasound transrectal needle biopsy revealed mesenchym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…The earliest case of SS of the prostate was reported by Iwasaki et al in 1999 in the American Journal of Surgical Pathology [1]. Through a literature search, we found that nine cases of prostate SS were clearly diagnosed by molecular studies in the English literature [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] . Together with our report, there were a total of 10 cases.…”
Section: Clinical Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The earliest case of SS of the prostate was reported by Iwasaki et al in 1999 in the American Journal of Surgical Pathology [1]. Through a literature search, we found that nine cases of prostate SS were clearly diagnosed by molecular studies in the English literature [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] . Together with our report, there were a total of 10 cases.…”
Section: Clinical Discussionmentioning
confidence: 94%
“…Prostate comply SS is extremely rare in clinical practice. The first case was reported by Iwasaki et al in 1999 [1] , and we retrieved nine cases in the English literature that were confirmed as primary SS of the prostate by molecular detection methods [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] . In the prostate biopsy, a case of prostate SS was found, which was confirmed to be prostate SS by immunohistochemistry and fluorescence in situ hybridization (FISH).…”
Section: Introduction and Importancementioning
confidence: 99%
“…5 Although in this case, no evidences of metastases were found. The radiological features of primary prostatic synovial sarcoma are not characteristic, which may present large hypoechoic lesion on ultrasound and soft tissue tumor with mixed cystic/solid components on CT. 2,5 The adrenocortical carcinoma is an aggressive tumor with poor 5-year survival rate, 6 and the majority of adrenocortical carcinoma, like this case, show hypermetabolism on 18 F-FDG PET/CT. 7,8 Here, we present a rare case of primary prostatic synovial sarcoma and combined adrenocortical carcinoma.…”
mentioning
confidence: 75%
“…In the time since Iwasaki and colleagues described the first known case of primary prostatic synovial sarcoma in 1999, only 11 total cases have been reported in the English literature to date. [7][8][9][10][11][12][13][14][15][16] We herein present what we believe is the 12th reported case of primary prostate synovial sarcoma on the basis of the published literature, and to our knowledge is only the second reported case of primary synovial sarcoma of the prostate with pulmonary metastatic disease at presentation.…”
Section: Introductionmentioning
confidence: 94%